Productive response and reproductive performance of dairy cows subjected to different feeding systems - Salado, Eloy Eduardo (2020)
Fifty Holstein cows (2.6 ± 1.0 lactations) in early lactation (52.6 ± 16.4 days in milk) calved in autumn and producing 34.3 (±4.4) kg milk per cow∙day−1 were randomly assigned for 27 weeks to one of two treatments (feeding systems) in 10 groups (pens) of 5 animals each (5 groups/treatment). The confined treatment was a total mixed ration (TMR_100) whereas the supplemented grazing system was defined by a partially mixed ration (PMR_75) with 75% TMR and 25% oat pasture ( Avena sativa L. ) during the autum-winter (Period I) and alfalfa pasture ( Medicago sativa L. ) plus concentrate (7.0 kg per cow∙day−1) (P + C) during the next spring (Period II). Milk production was daily and individually recorded throughout the trial while the chemical composition of milk was measured on individual samples every 2 weeks. Live weight (LW) and body condition score (BCS) using a scale of 1 to 5 were recorded every 3 weeks after the morning milking. Simultaneously, blood samples were taken for determinations of glucose, urea, non-esterified fatty acids (NEFA), insulin, somatotrophin (GH) and somatomedin C (IGF-I). Total DM intake was measured using the difference method four times per repetition in the months of July, August, September and October. The experimental herd was inseminated at fixed time at the start of the service (May-July) and on the return with estrus detection. The diagnosis of pregnancy was made by transrectal ultrasonography at 30 and 60 days after the start of the service. The productive data were analyzed according to a model with repeated observations in time adjusted by covariate with 2 periods and using the animal as the experimental unit. Data of DM intake were analyzed using ANOVA for 2 treatments with 5 repetitions. Cows from the TMR_100 group produced more milk (kg∙cow−1∙day−1) during Period I (33.7 vs. 32.3) and Period II (28.8 vs. 27.8) ( P < 0.01). Yields were also higher ( P < 0.05) in TMR_100 for milk fat (kg∙cow−1∙day−1) in Periods I (1.33 vs. 1.24) and II (1.10 vs. 0.92) and for milk protein (1.19 vs. 1.13 and 0.99 vs. 0.93). The lower energy intake of grazing cows (45.0 vs. 43.1 and 40.9 vs. 38.9 Mcal per cow∙day−1 for TMR_100 vs. PMR_75 and TMR_100 vs. P + C) coupled to the extra energy cost associated with grazing activity would explain the difference in milk production. Milk protein content (%) resulted higher ( P < 0.05) in TMR_100 over the two experimental periods (3.53 vs. 3.47 and 3.42 vs. 3.31) while milk fat content (%) was similar between TMR_100 vs. PMR_75 (3.90) but lower in P + C (3.30) compared to TMR_100 (3.87). The greatest LW gain (kg∙cow−1∙day−1) in the cows of the TMR_100 group in both periods (0.69 vs. 0.34 and 0.49 vs. −0.22) was consistent with the increase in the plasmatic levels of glucose and IGF-I and the reduction in the circulating levels of GH, but not with the lack of increases in plasma insulin concentration or decreases in circulating levels of NEFA, parameters that were not affected by treatments. Despite the positive effects of TMR_100 on parameters linked to energy balance, no significant differences were detected in any of the reproductive parameters evaluated and the final rate of pregnancy was 80.0 and 91.3% for the confined and grazing system with supplementation respectively. Free milk liters over feeding costs were higher in the grazing system with supplementation compared to the confined system (18.5 vs. 15.5 l, respectively). The results indicate that the grazing system with supplementation can be economically competitive compared to the confined system of milk production.